Empress Maria Theresa and the politics of Habsburg imperial art - Yonan, Michael Elia 1970- (Pennsylvania State Univ. Press, 2011)
"Explores the intersections between monarchy, gender, and art through an investigation of the visual and architectural culture of the eighteenth-century Habsburg empress Maria Theresa"--Provided by publisher.